Digitalität und Privatheit Kulturelle, politisch-rechtliche und soziale Perspektiven - Aldenhoff, Christian; Edeler, Lukas; Hennig, Martin; Kelsch, Jakob; Raabe, Lea; Sobala, Felix (Digitale Gesellschaft, 2019)
Privacy in the digital society - its forms, opportunities, and risks.